The athlete`s pharmacy - Ciocca, M.; Stafford, H.; Laney, R. (Clinics in Sports Medicine, 2011)
Athletes use a variety of substances for the treatment of pain, injury, common illnesses, or to gain an advantage in competition. A growing concern is that many young athletes may use potentially dangerous, but legal, medications without consulting health professionals. Physicians providing care for athletes should be aware of any medications that an athlete is taking and how these substances may interact with performance, exercise, environment, and other medicines. Moreover, it is vital that physicians are familiar with these medications so that athletes are properly educated on the potential benefits and/or risks, and how each substance may affect the body.